PROBLEMATIKA PELAKSANAAN PEMBELAJARAN HYBRID LEARNING PADA MATA PELAJARAN PPKn DI SMA NEGERI 16 SURABAYA - Hesti Veronica Putri; Maya Mustika Kartika Sari (Kajian Moral dan Kewarganegaraan, 2022)
The current implementation of hybrid learning is a new experience that has occurred at state 16 senior high school of Surabaya. In the implementation of hybrid learning is not an easy thing to do in a lesson, so that in its implementation it can bring up problems that occur in learning actors, namely teachers and students. This study aims to determine the problems faced by students and teachers of Civics in the implementation of hybrid learning at state 16 senior high school of Surabaya. The research method used is a combination research method (mixed method) with the type of Sequential Exploratory Design. The respondents in this study were 3 teachers of Civics and 90 students from class grade ten of math and science 2, grade eleven of math and science 7, and grade twelve of math and science 4 at state 16 senior high school of Surabaya with data collection techniques through observation, structured interviews with 3 Pancasila and civic education teachers and distributed questionnaires to 90 students. The results obtained, there are problems experienced by teachers and students in the implementation of hybrid learning on Civics subjects at state 16 senior high school of Surabaya, namely there are technical obstacles, such as (1) Lack of understanding of teachers in the field of technology, (2) Quality of Ms. Teams is not good, and (3) Constrained by internet network. This causes psychological problems for teachers and students to have difficulty in focusing on learning, so that it can lead to a lack of interaction between teachers and students. Keywords: Problematics, Hybrid Learning, Pancasila and Citizenship Education.